Retracted: Sirtuin 6 contributes to migration and invasion of osteosarcoma cells via the ERK1/2/MMP9 pathway - Hang Lin; Yi Hao; Zhengxu Zhao; Yongjun Tong (FEBS Open Bio, 2017)
Dysregulation of sirtuin 6 (SIRT6) is actively involved in tumor progression. High levels of SIRT6 have been associated with hepatocellular carcinoma and non‐small cell lung cancer, and SIRT6 facilitates growth and metastasis of cancer cells. However, the clinical significance and biological function of SIRT6 are not known for osteosarcoma (OS). Here, we report that SIRT6 was notably overexpressed in OS tissues compared with non‐cancerous specimens. The high level of SIRT6 was prominently correlated with malignant clinical parameters and poor prognosis of OS patients. SIRT6 was also up‐regulated in OS cells. SIRT6 knockdown inhibited the invasion and migration of Saos‐2 and U2OS cells in vitro, while SIRT6 restoration increased these cellular biological behaviors in MG‐63 cells. Mechanistically, SIRT6 up‐regulated expression of matrix metallopeptidase 9 (MMP9) in OS cells. MMP9 restoration partially abolished the effects of SIRT6 knockdown on OS cells, with increased cell migration and invasion. MMP9 knockdown reduced migration and invasion of SIRT6‐overexpressing MG‐63 cells. Furthermore, SIRT6 positively modulated the levels of phosphorylated extracellular signal‐regulated kinases 1 and 2 (ERK1/2). PD098059 and PD0325901, inhibitors of mitogen‐activated protein kinase kinase (MEK), blocked the regulatory effects of SIRT6 on p‐ERK1/2 and MMP9 levels, suggesting that SIRT6 regulated MMP9 abundance probably through the MEK–ERK1/2 pathway. These results suggest that SIRT6 may act as a prognostic predictor and a drug target for OS patients.